ANALISIS PENGUKURAN KINERJA MENGGUNAKAN BALANCED SCORECARD PADA HOTEL SEGARA LOMBOK LODGE - Sri Hartati; Ida Ayu Nursanty; Sofiati Wardah (PT Seval Literindo Kreasi, 2022)
The purpose of this study was to determine the performance of Hotel Segara Lombok Lodge in the four perspectives of the balance scorecard, namely the financial perspective, the customer perspective, the internal business process perspective, and the learning and growth perspective. This research is quantitative descriptive. Data was collected by collecting company documents and interviews with the director and operational manager of Hotel Segara Lombok Lodge. The results showed that from the financial perspective, Hotel Soon Lombok Lodge got a score of 9, from the customer perspective it got a value of 7, from the internal business process perspective it got a score of 8 and from the internal business perspective it got a value of 5 so that the total weighted value of the four balanced scorecard perspectives was 29. The results of the study showed that the performance of the Segara Lombok Lodge Hotel during the pandemic was considered quite well.